The role of CYP2E1 and 2B1 in metabolic activation of benzene derivatives - Gut, I; Nedelcheva, V; Soucek, P; Stopka, P; Vodicka, P; Gelboin, H V; Ingelman-Sundberg, M (Archives of toxicology, 1996)
CYP2B1 and 2E1 oxidized toluene, aniline and monochlorobenzene (MCB) to water-soluble metabolites and to products covalently binding to microsomal proteins from male Wistar rats at high efficiency. Oxidation of benzene to covalently binding metabolites was catalysed by CYP2B1 and 2E1 more effectively than the formation of water-soluble metabolites, especially at low benzene levels. Thus, the formation of covalently binding products was inversely related but formation of soluble metabolites was proportional to benzene concentration. 1,4-Benzoquinone was responsible for the majority of covalent binding to microsomal proteins, being suppressed by ascorbate; 1,4-semiquinone was not important, since alpha-tocopherol did not inhibit the covalent binding and ESR showed its rapid decay, if NADPH was available. Specific antibodies and inhibitors confirmed the role of CYP2B1 and 2E1 induction. Covalent binding of benzene to DNA was largely due to benzene oxide; approximately 50% was due to N-7 guanine adduct. CYP2E1 oxidizing benzene via phenol to 1,4-hydroquinone appeared to mediate its further oxidation to 1,4-benzoquinone, which also occurred spontaneously, but was reversed in a reducing environment of microsomes with NADPH. Production of OH radicals in microsomes with NADPH was greatly stimulated by HQ and less by BQ, especially in CYP2E1 induced microsomes, although the quinones themselves failed to produce OH radicals. The quinones could act by simulation of the CYP futile cycle. Therefore, CYP2B1 and 2E1 in rats appeared essential for metabolic activation of benzene derivatives to potentially genotoxic products; BQ dominated the covalent binding of benzene to proteins, whereas DNA adducts were largely due to benzene oxide.
Keywords: Animals; Rats; benzen; Rats, Wistar; DNA; Benzene; Carcinogens; jaterní mikrozomy; Cytochrome P-450 CYP2E1; Cytochrome P-450 CYP2B1; cytochrom P-450 CYP2E1; Male; karcinogeny; biotransformace; benzenové deriváty; Microsomes, Liver; krysa rodu Rattus; Biotransformation; Benzene Derivatives; zvířata; mužské pohlaví; cytochrom P-450 CYP2B1; potkani Wistar